Skin leiomyoma (clinical observation) - Yu. N. Grekova; N. V. Zilberberg; N. P. Toropova; E. I. Kuznetsova (Лечащий Врач, 2021)
The authors describe a clinical case of the rare tumor — skin leiomyoma in a 54-year-old patient. The authors describe clinical manifestations, differential diagnosis and pathomorphological picture of the disease.